Factors Associated with Poor Compliance of Antiepileptic Drugs in Children with Epilepsy: Poor Compliance of Antiepileptic Drugs in Children with Epilepsy - Kumar, Lalit; Kulsoom, Shazia; Hussain, Wajid (Pakistan Journal of Health Sciences, 2026)
Epilepsy is a chronic neurological disorder characterized by recurrent seizures resulting from abnormal electrical discharges in the brain. Objectives: To determine the factors associated with poor compliance with antiepileptic drugs in children with epilepsy. Methods: This cross-sectional study was conducted at the Outpatient Department of Neurology of the National Institute of Child Health, Karachi, Pakistan, from January 2025 to June 2025. A total of 185 children aged 1–12 years with epilepsy, diagnosed ≥6 months earlier, were recruited by non-probability consecutive sampling. Compliance with antiepileptic drugs was assessed using the Morisky Medication Adherence Scale (MMAS-8), classifying scores ≥6 as compliant. Factors behind non-compliance were noted. Data were analyzed using SPSS v26 with chi-square and binary logistic regression applied, taking p<0.05 as significant. Results: In a total of 185 children, the mean age was 7.4 ± 3.1 years, and 104 (56.2%) were males. Respondents were 117 (63.2%) mothers and 68 (36.8%) fathers, with a mean parental age of 34.8 ± 6.7 years. Residence was urban in 118 (63.8%), and rural in 67 (36.2%). Low socioeconomic status was noted in 92 (49.7%), and 47 (25.4%) parents were illiterate. Overall, 119 (64.3%) children were compliant and 66 (35.7%) non-compliant. Non-compliance was significantly associated with rural residence (AOR 1.9, 95% CI 1.0–3.6), low socioeconomic status (AOR 2.5, 95% CI 1.1–5.7), and illiteracy (AOR 6.9, 95% CI 2.4–20.5). Conclusions: Non-compliance with AEDs in children with epilepsy in Karachi was strongly influenced by rural residence, low socioeconomic status, and low parental education.